Diagnostic Utility of Bone Marrow Examination in Bicytopenia - V Shulbha Sejekan; K Sree Lakshmi; S Dayananda Biligi; BS Ramya (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Bicytopenias refer to condition in which either of the two cell lineages is reduced because of various diseases affecting the bone marrow. Bone marrow examination plays an important role aiding the peripheral smear and complete blood count findings in various haematological disorders. The present study has emphasised on the utility of bone marrow aspiration and bone marrow biopsies in cases of bicytopenias to assess the causative disease thus aiding for further clinical management. Aim: To study the cytomorphology of bicytopenia in peripheral smear and bone marrow examination and to estimate the utility of bone marrow examination in bicytopenia in arriving at the diagnosis of the disease. Materials and Methods: The present descriptive study was carried out in the Department of Pathology, Bangalore Medical College and Research Institute (BMCRI), Banglore, India, for a period of one year from April 2016 to April 2017. Total 80 confirmed cases of bicytopenias were included. Bone marrow aspiration, imprint smears and biopsy was performed for all cases. The parameters assessed after bone marrow aspiration and biopsy were on cellularity, myeloid to erythroid ratio, cytomorphological details of the cells. The data obtained was tabulated, descriptive statistics and Chi-square test was used for statistical analysis. Results: Out of total 80 subjects, age group ranged from two to 79 years. The bicytopenias observed in peripheral smear examination has been anaemia and thrombocytopenia in 88.75% of cases, followed by anaemia and leukopenia in 8.75% of cases, lastly followed by leukopenia and thrombocytopenia in 2.5% of cases. Bone marrow aspiration performed showed predominantly normoblastic maturation followed by megaloblastic maturation and micronormoblastic maturation. The bone marrow aspiration yielded cellular marrow in 75 cases and diluted marrow in five cases. Imprint smears and bone marrow biopsy was performed in all the cases. Out of five diluted aspiration both imprint smears and bone marrow biopsy revealed normoblastic marrow in three cases, single case showed myelofibrosis and a single case of non Hodgkin’s lymphoma. Conclusion: Bone marrow aspiration helps to understand the cytomorphological details. In cases with diluted marrow or dry tap, imprint smears along with bone marrow biopsies help to arrive at the diagnosis. So, they complement each other along with haematological parameters and clinical details to aid for a better clinical management of the patients.